The impact of travel nursing on patient outcomes and healthcare sustainability in Canada - McClymont, Megan; Bauknecht, Eva; Bosch, Mary; Kedziora, Konrad (My University, 2026)
Travel nursing in Canada has expanded rapidly since 2020 as a strategy to address staffing crises, yet its impact on care quality remains contested. This paper examines how the continually increasing use of travel nurses compared to units staffed exclusively by permanent nurses affects patient outcomes, hospital economics, safety, teamwork, and continuity of care. Drawing on recent Canadian and international literature, the analysis situates travel nursing within Donabedian’s (1988) Structure-Process-Outcome model to distinguish the effects of nurse employment status from underlying system factors such as staffing ratios, work environment, and onboarding practices. Evidence suggests that many adverse outcomes attributed to travel nurses are more strongly associated with inadequate staffing, high workload, and poor organizational culture. At the same time, heavy reliance on travel contracts introduces ethical and economic concerns, including wage disparities, team cohesion tensions, and operational inefficiencies. The paper concludes that travel nursing is an important but unsustainable compensatory mechanism, and that improving retention, staffing models, and workplace conditions is essential to optimize its role in a resilient Canadian nursing workforce.
Keywords: travel nursing; Canada; staffing crises; Canadian nursing workforce